A new species of Modisimus Simon (Araneae: Pholcidae) in Baja California Sur, Mexico - Jimenez, Maria-Luisa; Palacios-Cardiel, Carlos (Zootaxa, 2015)
The genus Modisimus Simon 1893 (Pholcidae) is distributed across the Americas from Venezuela to the USA, including the Caribbean Antilles, with an endemic species in the Galapagos Islands and one cosmopolitan species (World Spider Catalog 2015). Until now, 81 species of Modisimus have been described, of which 17 species are found in Mexico (World Spider Catalog 2015). In this paper, a new Mexican species is described. Modisimus species are mainly found in humid tropical forests in shady, humid places near the ground, with their webs extended between buttresses of trees, fallen logs, or rocks (Huber 1998), and only one species (M. vittatus Bryant, 1948) is found in city gardens, exposed road embankments, as well as among cacti and agaves in semi-arid scrubland (Huber et al. 2010). This genus is also common in caves where pholcids population can be abundant (Gertsch 1971, 1973, 1977; Valdez-Mondragón & Francke 2009).